Ammonium chloride effects on bismuth electrodeposition in a choline chloride-urea deep eutectic solvent. (20th January 2021) - Karar, Youcef; Boudinar, Salem; Kadri, Aziz; Leprêtre, Jean-Claude; Benbrahim, Nassima; Chaînet, Eric
Abstract: The ammonium chloride effect on bismuth electrodeposition from choline chloride-urea deep eutectic solvent (DES) was investigated. Spectroscopic and thermal studies were performed on the latter in order to understand whether the addition of ammonium chloride affects the DES behavior; the results of the thermal study do not indicate any significant change except a small shift in the melting point of the DES when adding the ammonium salt ( +3 °C) and the modification of a cold crystallization peaks at low scan rate. The electrochemical behavior of bismuth was then studied by cyclic voltammetry in the deep eutectic solvent with different NH4 Cl content. Bismuth electrocrystallization was studied by chronoamperometry which has shown that the bismuth electrodeposition in studied conditions evolves with a three-dimensional progressive nucleation. SEM images show that grain size of bismuth deposits decreases while adopting a well-defined geometry as ammonium salt concentration increases. EDS analysis confirms that pure bismuth thin films were obtained and X-Ray diffraction indicates that the bismuth growth follows a preferential orientation along the (012) reticular plane.